PENGUKURAN KINERJA DENGAN METODE BALANCED SCORECARD PADA BENOA MARITIME INDONESIA - I Made Sandi Koriada, I Made Dwi Budiana Penindra, Ni Luh Putu Lilis Sinta Setiawati, Anak Agung Ist (JURNAL RISET DAN APLIKASI TEKNIK INDUSTRI, 2023)
Performance measurement is an important thing that must be done by the company to evaluate and determine the level of success of the implemented strategy. There are companies that have never carried out performance measurements, one of which is Benoa Maritime Indonesia, so the company does not yet know how successful the strategy has been. The purpose of this study was to determine the performance of Benoa Maritime Indonesia based on measurements using the balanced scorecard method. The use of the balanced scorecard method in this study to emphasize the balance of assessment between various indicators, not only measures from one perspective but four perspectives in several financial perspectives, customer perspectives, internal business process perspectives, as well as learning and growth perspectives. In each balanced scorecard perspective there are different measurement indicators. The indicators used to measure the performance of Benoa Maritime Indonesia in this study are: 1) profit growth and return on assets (ROA) from a financial perspective, 2) customer acquisition and customer satisfaction from a customer perspective, 3) innovation process from an internal business process perspective, and 4) employee turnover, employee productivity, and employee satisfaction in the perspective of learning and growth. Based on the results of performance measurement in 2021 – 2022 at Benoa Maritime Indonesia, profit growth and ROA score -1 which indicates poor performance. In the innovation process, a score of 0 is included in the sufficient category. On customer acquisition, customer satisfaction, employee turnover, employee productivity, and employee satisfaction get a score of 1 which is included in the good category. Using the balanced scorecard method, an average score of 0.375 is obtained which indicates that Benoa Maritime Indonesia's performance is in the fairly good category.